2017
DOI: 10.1364/oe.25.016047
|View full text |Cite
|
Sign up to set email alerts
|

NaYF_4:Sm^3+/Yb^3+@NaYF_4:Er^3+/Yb^3+ core-shell structured nanocalorifier with optical temperature probe

Abstract: A core-shell structure with a NaYF:Sm/Yb core for photothermal conversion nanocalorifier and a NaYF:Er/Yb shell as temperature probe for potential applications in photothermal therapy (PTT) were synthesized by a thermal decomposition technique of rare-earth oleate complexes. The optical temperature reading-out property for the NaYF:Sm/Yb@NaYF:Er/Yb core-shell structure was systematically investigated and it was found that in comparison with pure NaYF:Er/Yb particles, the temperature sensing performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Among them, two strong green emissions centered at around 545 and 565 nm can be assigned to the 2 H 11/2 , 4 S 3/2  →  4 I 15/2 transitions, and the red emission ranging from 650 to 740 nm originates from 4 F 9/2  →  4 I 15/2 transition 28,29 . In addition, an extremely weak near infrared emission located at 820 nm corresponding to 4 I 9/2  →  4 I 15/2 transition can also be observed 30 . The inset of Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Among them, two strong green emissions centered at around 545 and 565 nm can be assigned to the 2 H 11/2 , 4 S 3/2  →  4 I 15/2 transitions, and the red emission ranging from 650 to 740 nm originates from 4 F 9/2  →  4 I 15/2 transition 28,29 . In addition, an extremely weak near infrared emission located at 820 nm corresponding to 4 I 9/2  →  4 I 15/2 transition can also be observed 30 . The inset of Fig.…”
Section: Resultsmentioning
confidence: 95%
“…A similar system was proposed by Tong et al 133 employing Sm 3+ ions as heating centres. As in the structure developed by Ximendes et al, the heating agent is placed in the core and the thermal sensitive Er 3+ ions are allocated at the shell.…”
Section: E3 Core-shell Rare Earth-doped Nanoparticles For Photothermentioning
confidence: 92%
“…12 When rst developed, luminescence ratiometric thermometry involved thermally coupled energy levels (TCELs) of rare earth and transition metal ions. [13][14][15][16][17][18] Sui et al prepared a Tm 3+ /Yb 3+co-doped LiYF 4 single crystal and found that the intensity ratio between the 3 F 2 / 3 F 3 -3 H 6 and 3 H 4 -3 H 6 transitions of Tm 3+ could be used for temperature determination. 19 Rakov et al demonstrated that the 2 F 5/2 Stark sublevels of Yb 3+ and the 4 I 13/2 Stark sublevels of Er 3+ were both TCELs, based on which they successfully measured the temperature.…”
Section: Introductionmentioning
confidence: 99%